Determinants of Firm Value with Environmental Performance as a Moderating - Kuncoro, Ignatius Bayu; Sihombing, Pardomuan (Research of Business and Management, 2025)
This research examines the influence of Leverage, Liquidity, Profitability, and Institutional Ownership on Firm Value, with Environmental Performance as a moderating variable. The study focuses on coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using purposive sampling, 14 companies were selected as research samples. Panel data regression analysis was employed. The findings reveal that Leverage and Institutional Ownership do not affect Firm Value. Liquidity negatively affects Firm Value, while Profitability has a positive impact. Environmental Performance does not directly influence Firm Value but moderates certain relationships. Specifically, Environmental Performance strengthens the effect of Liquidity and Profitability on Firm Value but does not moderate the impact of Leverage. The study’s managerial implications highlight the importance of fundamental factors such as profitability, leverage, and dividend policy in enhancing Firm Value. Additionally, companies should recognize Environmental Performance as a moderating factor that can reinforce certain financial influences. Management is encouraged to adopt sustainable business practices to improve both financial performance and environmental responsibility.